The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/mnras/stx722
|View full text |Cite
|
Sign up to set email alerts
|

Red but not dead: unveiling the star-forming far-infrared spectral energy distribution of SpARCS brightest cluster galaxies at 0 < z < 1.8

Abstract: We present the results of a Spitzer/Herschel infrared photometric analysis of the largest (716) and highest-redshift (z = 1.8) sample of Brightest Cluster Galaxies (BCGs), those from the Spitzer Adaptation of the Red-Sequence Cluster Survey (SpARCS). Given the tension that exists between model predictions and recent observations of BCGs at z < 2, we aim to uncover the dominant physical mechanism(s) guiding the stellar mass buildup of this special class of galaxies, the most massive in the Universe and uniquely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 140 publications
13
37
0
Order By: Relevance
“…Optical and near-infrared data show that the color evolution of BCGs is in good agreement with a passive population synthesis model (Stott et al 2008;Whiley et al 2008;Wen & Han 2011). However, several studies show signatures of ongoing star formation or active galactic nuclei (AGN) in some BCGs (Crawford et al 1999;McNamara et al 2006;Liu et al 2012;Fraser-McKelvie et al 2014;Green et al 2016;Donahue et al 2017;Bonaventura et al 2017). Previously, we found that richer clusters host more luminous BCGs at redshifts z < 0.42 (Wen et al 2012).…”
Section: Evolution Of Bcgssupporting
confidence: 76%
“…Optical and near-infrared data show that the color evolution of BCGs is in good agreement with a passive population synthesis model (Stott et al 2008;Whiley et al 2008;Wen & Han 2011). However, several studies show signatures of ongoing star formation or active galactic nuclei (AGN) in some BCGs (Crawford et al 1999;McNamara et al 2006;Liu et al 2012;Fraser-McKelvie et al 2014;Green et al 2016;Donahue et al 2017;Bonaventura et al 2017). Previously, we found that richer clusters host more luminous BCGs at redshifts z < 0.42 (Wen et al 2012).…”
Section: Evolution Of Bcgssupporting
confidence: 76%
“…For the purposes of our analysis here we do not focus on the ICM or BCG evolution during this merger, which is still ongoing at z = 0, but analysis of the impact of this event will be the focus of future work. The star formation history of the BCG is remarkably similar to the median sSFR values presented in Bonaventura et al (2017), which are derived from IR detections of clusters. The McDonald et al (2016) results use multiple methods to estimate star formation at various wavelengths, but find that cool core clusters have systematically higher SFRs compared to their overall sample, which could explain why RomulusC, which maintains a cool core until z ∼ 0.2, would also have comparatively more star formation.…”
Section: The Connection Between Agn Feedback and Bcg Quenchingsupporting
confidence: 75%
“…The peak of activity beginning around 8 Gyr and persisting through 10 Gyr is associated with the final quenching of the BCG. The sSFR history of the RomulusC BCG is remarkably close to the average evolution observed in clusters fromBonaventura et al (2017), but slightly high compared to results fromMcDonald et al (2016). The range in time shown is cut off just prior to the infall of the group seen inFigure 7.…”
supporting
confidence: 61%
“…However, the predicted growth seems to be somewhat larger than observed. This possible tension could be worsened by recent claims, based on FIR data, that BCGs exhibit a star formation activity at z 1 more significant than previously thought, and thus contributing in a non-negligible way to their late mass growth (Bonaventura et al 2017).…”
Section: Introductionmentioning
confidence: 92%